Can Transarterial Chemoembolization of Hepatocellular Carcinoma Result in Transformation to Combined Hepatocellular-Cholangiocarcinoma with Stem Cell Features? A Case Study - Joneja, MD, Upasana; Hann, MD, FAASLD, Hie-Won; Brown, MD, Daniel B.; Littman, MD, Susan J.; Baliff, MD, Jeffrey P. (North American Journal of Medicine and Science, 2017)
Transarterial chemoembolization (TACE) is currently one of the favored treatment modalities for non-curative hepatocellular carcinoma (HCC) and can be used to shrink tumor size in order to make a patient eligible for transplantation. Furthermore, with the advent of effective antiviral drugs for hepatitis B virus (HBV), concomitant antiviral therapy with local tumor ablation including TACE for HBV-associated HCC has been successful for long term survival. Over the last decade, however, concern has been raised about a phenomenon whereby a subset of TACE-treated HCCs becomes more aggressive after TACE treatment. One current hypothesis is that TACE eliminates only the hepatocellular cells and that hepatic progenitor cells that have the potential for developing to cholangiocarcinoma are then selected for and induced to proliferate post-TACE with possible dual differentiation along hepatocellular and biliary lines. We present a case of a patient with HCC who underwent TACE and subsequently experienced tumor regrowth as biopsy-proven combined hepatocellular-cholangiocarcinoma. Furthermore, we provide immunohistochemical evidence of hepatic progenitor cells in the post-TACE tumor biopsy, possibly accounting for its aggressive course. [N A J Med Sci. 2017;10(4):181-186. DOI: 10.7156/najms.2017.1004181]